Distribution pattern and ecological risk assessment of heavy metals in Henan section of the Yellow River - Zhang, Kai; Li, Kuangjia; Xin, Rui; Xu, Zhiheng; Zhang, Zhongshuai; He, Siyu; Zhao, Zhenzhen; Tong, Minghui; Cui, Yongxin (Water science & technology. Water supply, 2022)
Heavy metals (HMs) pollution in the environment is a persistent issue and draws public attention constantly. However, there is little research assessing the pollution level of HMs in the Henan section of the Yellow River although the river is one of the most important water supply rivers in Henan province. In this research, the fraction contents of six HMs in the Henan section of the Yellow River were investigated by adopting the European Community Bureau of Reference (BCR) sequential extraction procedure. Moreover, the potential health risk caused by HMs was evaluated by adopting both the geo-accumulation index (Igeo) and ecological hazard index method. The results indicate the presence of a light HM pollution level in the Yellow River generally. However, the health risk caused by Cd cannot be neglected. Fraction analysis indicates that the content of the B2 fraction is high, which needs more attention. Overall, branch afflux might be one of the important pathways through which anthropogenic activities influence the Yellow River. The results of both the Igeo and ecological hazard index indicate that the potential health risk caused by HMs is low in the Yellow River, and the Yellow River protection policies implemented by Henan province may be the underlying reason.